Correlation of computed tomographic signs of hypoperfusion and clinical hypoperfusion in adult blunt trauma patients. Issue 6 (June 2015) - Smithson, Lauren; Morrell, Joseph; Kowalik, Urszula; Flynn, William; Guo, Weidun Alan
Abstract : BACKGROUND: The computed tomographic signs of hypoperfusion (CTSHs) have been reported in radiology literature as preceding the onset of clinical shock in children, but its correlation with tenuous hemodynamic status in adult blunt trauma patients has not been well studied. We hypothesized that these CT findings represent a clinically hypoperfused state and predict patient outcomes. METHODS: We retrospectively reviewed 52 adult blunt trauma patients who presented to our Level I trauma center with an Injury Severity Score (ISS) greater than 15 and a systolic blood pressure less than 90 mm Hg and who underwent torso CT scans during a period of 5.5 years. Patient's demographics and clinical data were recorded. All CT scans were assessed by our radiologist (J.M.) for 25 CTSHs. RESULTS: Seventy-nine percent of the patients studied exhibited CTSH. The mean number of signs identified per patient was 4. Patient with the most common CTSH, that is, free peritoneal fluid, small bowel enhancement, flattened inferior vena cava (IVC), and flattened renal veins, had a significantly higher intensive care unit admission rate than those without (all p < 0.05). Patient with signs of small bowel abnormal enhancement/dilation, flattened IVC/renal vein had worse acidosis (all p < 0.05). A significantly lower admission hemoglobin and an increased need for red blood cell transfusion were found in patient with flattened IVC ( p < 0.05), flattened renal vein ( p < 0.01), and active contrast extravasation ( p < 0.01). Univariate analysis identified small bowel dilatation and splenic injury as factors associated with mortality and laparotomy, respectively. Logistic regression model revealed that splenic injury is a significant independent predictor of laparotomy (odd ratio, 7.50; 95% confidence interval, 1.67–33.71; p < 0.01). CONCLUSION: CTSH correlates with clinical hypoperfusion in blunt trauma patients and has important prognostic and therapeutic implications. The presence of CTSH in blunt trauma patients should draw immediate attention and require prompt intervention. Trauma surgeons should be familiar with these signs and include them in the clinical decision-making paradigms to improve outcomes in blunt trauma. LEVEL OF EVIDENCE: Diagnostic study, level III. Abstract : Supplemental digital content is available in the text.